Iron Deficiency Anaemia and Its Predisposing Causes Among Women Undergoing Antenatal Checkup at A Tertiary Care Hospital in Allahabad - Shweta Rajput; Manish Kumar Singh (National Journal of Community Medicine, 2016)
Background: Anaemia is a major health problem affecting about 50% of pregnant women and associated with poor pregnancy out- come.